The Differential Biopsychosocial Burden of Psoriasis and Vitiligo: A Comparative Analysis of Participation Restriction and its Clinical and Psychiatric Correlates - Nurrachmat Mulianto; Shelly Lavenia Sambodo; Muhammad Eko Irawanto; Arie Kusumawardani (Open Access Indonesian Journal of Medical Reviews, 2025)
Visible skin diseases like psoriasis vulgaris and vitiligo impose a significant psychosocial burden. However, the comparative impact on real-world functioning and the interplay of clinical, social, and psychiatric factors remain poorly understood, particularly in non-Western populations. This study aimed to quantitatively compare participation restriction between these two conditions and to identify its key biopsychosocial predictors. This comparative cross-sectional study, conducted in a tertiary Indonesian hospital, enrolled 50 patients (25 with psoriasis vulgaris, 25 with non-segmental vitiligo). The primary outcome was participation restriction, measured by the 18-item Participation Scale (P-Scale). Clinical severity was assessed using the Psoriasis Area and Severity Index (PASI) and Vitiligo Area Scoring Index (VASI). Crucially, depressive and anxiety symptoms were screened using the Patient Health Questionnaire-9 (PHQ-9) and Generalized Anxiety Disorder-7 (GAD-7) scale, respectively. A hierarchical multiple linear regression analysis was performed to identify predictors of participation restriction. Patients with psoriasis reported profoundly higher mean P-Scale scores (43.16 ± 5.01) compared to those with vitiligo (25.72 ± 4.21; p < 0.001), indicating more severe restrictions. Psoriasis patients also exhibited significantly higher scores for depressive symptoms (PHQ-9: 11.52 ± 3.18 vs. 5.68 ± 2.29; p < 0.001) and anxiety symptoms (GAD-7: 10.24 ± 2.95 vs. 5.12 ± 2.15; p < 0.001). The hierarchical regression model was highly significant (F(7, 42) = 28.14, p < 0.001), explaining 82.4% of the variance in P-Scale scores. After controlling for demographic and clinical factors, a diagnosis of psoriasis (β = 0.45, p < 0.001), higher clinical severity (β = 0.28, p = 0.002), and higher depressive symptom severity (PHQ-9 score; β = 0.39, p < 0.001) were significant independent predictors of greater participation restriction. In conclusion, psoriasis vulgaris is associated with a dramatically greater burden of participation restriction than vitiligo. This burden is driven by a complex interplay of the disease's clinical severity, its inherent diagnosis-specific factors, and, critically, comorbid depressive symptoms. These findings underscore the necessity of a biopsychosocial approach in dermatology, advocating for routine mental health screening and integrated care models to address the multifaceted drivers of disability in patients with chronic inflammatory skin disease.